2015
DOI: 10.1371/journal.pone.0128994
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Red Cell Distribution Width and Fibroblast Growth Factor 23 Cleaving in Patients with Chronic Kidney Disease and Heart Failure

Abstract: ObjectiveIn chronic kidney disease (CKD), both anemia and deregulated phosphate metabolism are common and predictive of adverse outcome. Previous studies suggest that iron status influences phosphate metabolism by modulating proteolytic cleavage of FGF23 into C-terminal fragments. Red cell distribution width (RDW) was recently identified as a strong prognostic determinant for cardiovascular morbidity and mortality, independently of iron status. We assessed whether RDW is associated with FGF23 cleaving in CKD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…9 Observational studies in humans have also demonstrated an inverse relationship between markers of iron status and cFGF23 levels. [10][11][12][13] Moreover, administration of intravenous iron in iron-deficient anemic women resulted in markedly decreased circulating cFGF23 concentrations, 14 consistent with the notion that ID is an important physiologic regulator of increased cFGF23 levels.…”
supporting
confidence: 59%
“…9 Observational studies in humans have also demonstrated an inverse relationship between markers of iron status and cFGF23 levels. [10][11][12][13] Moreover, administration of intravenous iron in iron-deficient anemic women resulted in markedly decreased circulating cFGF23 concentrations, 14 consistent with the notion that ID is an important physiologic regulator of increased cFGF23 levels.…”
supporting
confidence: 59%
“…Third, we were able to show that cFGF23 numerically outperforms iFGF23 in univariate and partially Cox-adjusted regression models. All previous prospective epidemiological studies among non-dialysis CKD patients focused upon cFGF23, and did not measure iFGF23 [3][4][5][6][7]; iFGF23 measurements are available from cross-sectional CKD cohorts [33][34][35]. Interestingly, the ratio iFGF23 to cFGF23 only marginally correlates with eGFR, which disputes the idea that splicing of iFGF23 into inactive fragments is substantially reduced as renal function deteriorates and that nearly all FGF23 is biologically active in advanced CKD [36].…”
Section: Discussion/conclusionmentioning
confidence: 97%
“…C-terminal FGF23 concentration has been reported to have not only a strong linear correlation with intact FGF23 concentration [ 8 ], but also an association with adverse cardiovascular and renal events [ 37 , 38 ]. On the other hand, recent studies suggested an increase in C-terminal FGF23 may precede an increase in intact FGF23 in the relatively early phase of CKD [ 39 ] and that cleavage of FGF23 might be a major determinant for FGF23 activity in various diseases [ 40 , 41 , 42 ]; therefore, serum levels of intact FGF23 should be assessed, especially among populations including patients without severe renal dysfunction, such as the current study sample.…”
Section: Discussionmentioning
confidence: 99%